Thermal resistance of rotating closed-loop pulsating heat pipes effects of working fluids and internal diameters - Niti Kammuang-Lue (2018)
© 2017 Society of Thermal Engineers of Serbia. The objective of this study was to experimentally investigate the effects of working fluids and internal diameters on the thermal resistance of rotating closed-loop pulsating heat pipes (RCLPHP). The RCLPHP were made of a copper tube with internal diameters of 1.50 mm and 1.78 mm, bent into the shape of a flower petal, and arranged into a circle with 11 turns. The evaporator section was located at the outer end of the tube bundle. R123, ethanol, and water were filled as the working fluids. The RCLPHP was rotated at centrifugal accelerations 0.5, 1, 3, 5, 10, and 20 times of the gravitational acceleration considered at the connection between the evaporator and the condenser sections. The heat input was varied from 30 W to 50 W, and then to 100 W, 150 W, and 200 W. It can be concluded that when the latent heat of evaporation increases, the pressure difference between the evaporator and the condenser sections decreases, and the thermal resistance increases. Moreover, when the internal diameter increases, the driving force increases and the frictional force proportionally decreases, or the Karman number increases, and the thermal resistance decreases.